Brazilian dentistry profiles and workforce - Saliba, Nemre Adas [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Prado, Rosana Leal do [UNESP]; Moimaz, Suzely Adas Saliba [UNESP] (My University, 2012)
The aim of this study was to assess the dentistry profile, based on social and demographic data, post-graduation formation, and to verify the insertion of dental graduates in the labour force. The participants were professionals graduated from a Brazilian Public Dental School, between 2000 and 2010. An instrument was sent by mail and/or e-mail to them. It was used Kruskal Wallis Test. Among 1047 questionnaires, 189 returned and 65.6% were answered by female. In relation to post-graduation course, 57.7% of professionals performed it, however 56.9% not attended only in their area; 66.6% of professionals are concentrated in cities larger than 100 thousand habitants. There was association between income and gender, and others. The predominant work modality was self-employed. Among the total, 36.5% want to work part-time in dentistry. The female gender was predominant and there was wage discrepancy between genders. The professionals have been concentrated in largest cities.
Keywords: Dentistry; Labour force; Dental staff